2021
DOI: 10.12669/pjms.37.3.3898
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ABCB1 gene polymorphism on concentration to dose ratio and adverse effects of tacrolimus in Pakistani liver transplant recipients

Abstract: Objective: To evaluate the possible association of ABCB1 single nucleotide polymorphism (SNPs) of the ABCB1 gene with tacrolimus dosages, concentration-to-dose ratios (CDR) and adverse effects in Pakistani liver transplant recipients. Methods: This observational study was conducted at Shifa International Hospital, Shifa Tameer-e-Millat University, Islamabad and Basic Medical Sciences Institute, Karachi from September 2016 to July 2020. Eighty-one liver transplant recipients were included. Demographics, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Where the values were one-third as compared to CC-smokers & non-smokers. These were consistent with the results of Blake CM et al 21 who presented analysis on pharmacokinetics of metaprolol and with Woo 13 who reported influence of genetic polymorphism on pharmacokinetics of drugs. The largest clearance observed in AA smokers group further augments the proposal of making a special strategy for dosing of rasagiline in this particular group.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Where the values were one-third as compared to CC-smokers & non-smokers. These were consistent with the results of Blake CM et al 21 who presented analysis on pharmacokinetics of metaprolol and with Woo 13 who reported influence of genetic polymorphism on pharmacokinetics of drugs. The largest clearance observed in AA smokers group further augments the proposal of making a special strategy for dosing of rasagiline in this particular group.…”
Section: Discussionsupporting
confidence: 91%
“…The results were consistent with Woo HI et al 12 who found genetic association with pharmacokinetics of atorvastatin and findings of Azam F et al identifying the role of ABCB1 polymorphism in achieving optimal levels of tacrolimus during dose titration. 13 CYP enzymes alter pharmacokinetics of drugs. Javed A reported side effects of chloroquine when given in combination with CYP3A4 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The P-glycoprotein (P-gp) transporter, which is encoded by theABCB1 transporter gene (also known as the MDR1 gene), is widely distributed in intestinal epithelial cells, liver cells, and renal proximal tubule epithelial cells 1 . Previous studies have shown that ABCB1 may affect tacrolimus absorption, distribution, and excretion 2,3 . Thus, some studies have focused on evaluating the relationship between ABCB1 gene polymorphism (1236C>T, rs1128503, Gly412Gly; 677G>T/A, rs2032582, Ala893DSer/Thr; 3435C>T, rs1045642, Ile1145Ile of exons 12, 21, and 26) and tacrolimus pharmacokinetics 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that ABCB1 may affect tacrolimus absorption, distribution, and excretion 2,3 . Thus, some studies have focused on evaluating the relationship between ABCB1 gene polymorphism (1236C>T, rs1128503, Gly412Gly; 677G>T/A, rs2032582, Ala893DSer/Thr; 3435C>T, rs1045642, Ile1145Ile of exons 12, 21, and 26) and tacrolimus pharmacokinetics 3,4 . However, the findings of these studies are inconsistent as concerns both SNPs and haplotypes, and systematic mechanistic studies to support their conclusions are still lacking.…”
Section: Introductionmentioning
confidence: 99%